(untitled) (Research, Society and Development, 2022)
This literature review aims to explain questions about the intensive rearing strategy of beef calves confined at the time of rearing, especially during the dry season, with emphasis on the intensification of rearing and reduction of grazing pressure. In Brazil, the predominant production system in beef cattle raising is the extensive system in which the base is mainly in tropical and temperate pastures, still with difficulty for technicians to transfer technology, information to the producer. use of food supplementation and mineral salt. In this scenario, there is no substantial investment, and simultaneously another factor to be considered is the dry season, in which the animals are unable to obtain positive results with reasonable weight gains, or even their own maintenance of body performance. In order for the termination to occur more quickly throughout the entire process, the intensification of feedlot calves in the rearing has been used, as this category presents a lower nutritional requirement, therefore, supplementation and monitoring is often not prioritized, as well as at the time of adaptation to weaning for the passage of its first drought to pasture to be replaced by rescue. So, the proposed breeding food strategy favors the system as a whole as a way of planning and optimizing results and reducing the stocking rate at more critical moments.